PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN STRES KERJA TERHADAP PRODUKTIVITAS KARYAWAN DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL MEDIASI DI PT. TIGAMAS MITRA SELARAS GRESIK - Anisa Rohmanita Dewi; Sunarto; Achmad Junaidi (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
in today's increasingly competitive business environment organization face growing complexities, particlurly in sustaining employee productivity amif external pressure such as market competition and demands for innovation and internal issues, including employee well-being and leadership quality. productivity plays a pivotal role in organizational succser, shaping profitability, operational efficiency, and competitiveness. a key derminant is employee well being, with job stress frequently exerting a detrimental effect. prolonged increased absenteeism, thereby undermining organizational productivity. this study examines the effects of transformational egagement as a mediating variable, at PT Tigamas Mitra Selaras Gresik. The objective is to analysze how transformational leadership and kob stress, both directly and through the mediation of employee comprising the entire population (n=36) was employed; data were collected viar suvey and analyzed using partial least squares (PLS). the findings indicate that transformational leadership has a positive effect on productivity and employee engagement, whereas excessive kobn stress exarts a negative impact on both engagement and productivity. Moreocer, employee engagement signifianctly mediates the relationship between transfromational leadership and productivty and between job steess and productivty. the study recommends the development of transformational leadership and the impementation of robust stress-management strategies as critical avenues for enhancing productivity. accordingly, organizations should institute transformational leadership training to strengthen engagement and introduce stress-mnanagement initiatives grounded in psychological support and more collaborative work environment. this study offers practical constributions to human resource management praticulary importance of balancing insipirational leaderhsip with reduction of work-elected pressures.